2021
DOI: 10.1177/00027642211003149
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic and the Rental Market: Evidence From Craigslist

Abstract: Past research has demonstrated the racially and spatially uneven impacts of economic shocks and environmental disasters on various markets. In this article, we examine if and how the first few months of the COVID-19 pandemic affected the market for rental housing in the 49 largest metropolitan areas in the United States. Using a unique data set of new rental listings gathered from Craigslist and localized measures of the pandemic’s severity we find that, from mid-March to early June, local spread of COVID-19 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…Although the aforementioned studies linked COVID-19 and housing prices, there is still uncertainty surrounding the impact of COVID-19 on the housing market [31]. Very few studies in literature have investigated the spatial heterogeneity of the impact of the COVID-19 pandemic on housing markets [32][33][34]. However, housing prices may be affected heterogeneously across different counties in the U.S., due to the uneven distributions of some socio-economic factors, such as average household size, percentage of households with Internet at home, education, and poverty variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the aforementioned studies linked COVID-19 and housing prices, there is still uncertainty surrounding the impact of COVID-19 on the housing market [31]. Very few studies in literature have investigated the spatial heterogeneity of the impact of the COVID-19 pandemic on housing markets [32][33][34]. However, housing prices may be affected heterogeneously across different counties in the U.S., due to the uneven distributions of some socio-economic factors, such as average household size, percentage of households with Internet at home, education, and poverty variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Not all rental hous ing in the United States is adver tised on Craigslist; indeed, Boeing (2020) found that adver tise ments for rental hous ing on Craigslist in Unequal Availability of Rental Housing Information 2014 were over rep re sented in neigh bor hoods with higher shares of White res i dents, dem on strat ing how offline inequalities are reproduced in the sup ply of infor ma tion online. However, our goal is to under stand what kind of infor ma tion is shared on Craigslist, the most com pre hen sive and timely source of hous ing mar ket infor ma tion in the United States (Boeing and Waddell 2017;Kuk et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Similar conclusions were reached by Trojanek et al (2021) , who estimated that housing rents in Warsaw fell by 7.7% between March and December 2020. Finally, the analysis conducted by Kuk et al (2021) showed that in the period immediately after the coronavirus outbreak—namely, from mid-March to early June 2020—apartment rental prices in the U.S. dropped by several percent.…”
Section: Literature Reviewmentioning
confidence: 99%